2022
DOI: 10.3389/feart.2022.1015460
|View full text |Cite
|
Sign up to set email alerts
|

Experimental analysis of dissolution reconstruction of deep dolomite reservoirs: A case study of the Cambrian dolomite reservoirs in the Tarim Basin

Abstract: The deeply buried carbonate reservoir of Cambrian is an important target of oil and gas exploration in the Tarim Basin. Understanding the dissolution mechanism of the deep-buried carbonate reservoir is an urgent problem to be solved. In this study, 11 carbonate samples from three types of deep reservoirs in Tarim Basin were selected as experimental objects, and the dissolution process of carbonate reservoir was simulated by using an advanced reaction system of continuous flow at high temperature and high press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…Zhang et al studied the flow and dissolution process of acetic acid and CO 2 solution in carbonate pores and found that the sample dissolved and the permeability increased by almost 12.5 times. CO 2 can increase formation permeability, but CO 2 may also clog the formation.…”
Section: Co2 Floodingmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al studied the flow and dissolution process of acetic acid and CO 2 solution in carbonate pores and found that the sample dissolved and the permeability increased by almost 12.5 times. CO 2 can increase formation permeability, but CO 2 may also clog the formation.…”
Section: Co2 Floodingmentioning
confidence: 99%
“…Meanwhile, an acidic environment can corrode carbonate cement in carbonates and sandstones, thereby improving formation permeability. 44 Zhang et al 53 studied the flow and dissolution process of acetic acid and CO 2 solution in carbonate pores and found that the sample dissolved and the permeability increased by almost 12.5 times. CO 2 can increase formation permeability, but CO 2 may also clog the formation.…”
Section: Co 2 Floodingmentioning
confidence: 99%